2005
DOI: 10.1016/j.bcp.2005.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the Ala67Thr polymorphism in agouti related protein associated with anorexia nervosa and leanness

Abstract: AgRP is a neuropeptide that stimulates food intake through inhibition of central melanocortin receptors (MCRs). In humans, the nonconservative amino acid substitution Alanine (Ala) 67 Threonine (Thr) has been associated with Anorexia Nervosa and with leanness. In the present study, the cellular distribution, processing and in vitro and in vivo activities of Ala67 and Thr67 AgRP were investigated. Western blots of media and lysates of BHK cells stably transfected with Ala67 or Thr67 expression constructs showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…As AGRP is an endogeneous antagonist of hypothalamic melanocortin-4 receptor (MC4R) and stimulates feeding and weight gain, an alanine to threonine substitution at codon 67 might result in inadequate blockade of the MC4R with a consequently lower stimulation in food intake (Vink et al, 2001). But functional analysis of this polymorphism did not demonstrate a defect of Thr67AgRP related to MC4R interactions (de Rijke et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…As AGRP is an endogeneous antagonist of hypothalamic melanocortin-4 receptor (MC4R) and stimulates feeding and weight gain, an alanine to threonine substitution at codon 67 might result in inadequate blockade of the MC4R with a consequently lower stimulation in food intake (Vink et al, 2001). But functional analysis of this polymorphism did not demonstrate a defect of Thr67AgRP related to MC4R interactions (de Rijke et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…The Ala67Thr polymorphism in the Agrp gene has been associated with greater risk of developing AN (Vink et al, 2001). Functional analysis of this polymorphism in a cell line showed that this polymorphism did not lead to dysfunction of Agrp ’s ability to inhibit alpha-MSH induced activation of the MC4 receptor (de Rijke et al, 2005b), suggesting that this polymorphism may indirectly affect food intake via other actions of Agrp signaling in AN patients. Our finding of altered Agrp expression in rats vulnerable to weight loss in the ABA paradigm may allow for mechanistic studies to determine the exact role Agrp has in AN.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, homozygosity for the Thr67 allele is associated with low body fat mass and low lean body mass, while the Ala67 allele is associated with late-onset obesity. Although the Thr67 variation results in no detectable change in binding to the MC4R or sorting efficiency into and secretion from DCGs, the polarity of the amino acid substitution may cause a conformational change in AgRP, affecting other peptide functions that need further characterization (28). …”
Section: Reported Snps In Genes Encoding Secreted Proteins That Are Amentioning
confidence: 99%